RISK ASSESSMENT MODEL FOR CORONARY ATHEROSCLEROSIS IN PATIENTS WITH VISCERAL OBESITY - N. G. Veselovskaya; G. A. Chumakova; N. N. Shenkova; E. S. Osipova; O. V. Gritsenko (Российский кардиологический журнал, 2015)
Aim. To invent a model for coronary atherosclerosis risk prediction in patients with visceral obesity and to conduct comparison research for this model with the other known Framingham and PROCAM.Material and methods. Totally 67 men included, of the age 40-65 (50,95±6,54 y.o.) without angina pectoris and clinical signs of another localization atherosclerosis. Patients had general obesity of I-III grade with BMI 35,16±3,32 kg/m , and visceral obesity by the thickness of epicaridal fat >7 mm. After coronary arteriography or multidetector computed tomography of coronary arteries we selected 2 comparison groups: group I (n=25) — patients with coronary atherosclerosis, group II (n=42) — without. For the invention of the prognostic score we used regression model with regression and optimal scaling.Results. Potential predictors of coronary atherosclerosis riskas a result of two groups comparison were: arterial hypertension, carbohydrate metabolism disorders, triglycerides, leptin, adiponectin and C-rective protein. As the result of regression analysis each predictor got its own significance mark. The rate of correctclassifications reached 79,1% that shows good prognostic value of this regression model. While using Framingham and PROCAM model the prognostic value of subclinical coronary atherosclerosis was 24,6% and 21,6% lower, resp., than the new risk assessment. Conclusion. The model invented of the risk assessment in visceral obesity patients makes it possible to take into account the main pathogenetic mechanisms that connect obesity and coronary atherosclerosis.